Psychological rehabilitation of law enforcement officers after the use of firearms - O. V. Markov; Ye. P. Tenenov; S. M. Butryk; A. М. Kozynets (Bulletin of Kharkiv National University of Internal Affairs)
Alongside the global evolution in societal relations, characterized by the advancement of democratization and the humanization of the social environment, the protection of citizens’ rights and freedoms has become paramount. In this context, the psychological well-being of law enforcement officers stands out as a critical concern, shaped by a multitude of factors. The intensity of this issue is magnified in countries experiencing military conflict, as the psychological burden on Ukrainian law enforcement personnel has escalated dramatically due to ongoing warfare.